2013
DOI: 10.1038/bcj.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin dephosphorylation/downregulation contributes to ursolic acid-mediated cell death in human leukemia cells

Abstract: Ezrin links the actin filaments with the cell membrane and has a functional role in the apoptotic process. It appears clear that ezrin is directly associated with Fas, leading to activation of caspase cascade and cell death. However, the exact role of ezrin in ursolic acid (UA)-induced apoptosis remains unclear. In this study, we show for the first time that UA induces apoptosis in both transformed and primary leukemia cells through dephosphorylation/downregulation of ezrin, association and polarized colocaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…After 4 weeks of treatment, mice were killed by cervical dislocation, and tumour tissues were harvested and fixed in 4% paraformaldehyde or frozen at −80°C. Histological, immunohistochemical and immunofluorescence analyses were performed as described . TdT‐mediated dUTP nick‐end labelling (TUNEL) analysis was used to detect the dead cells in the tissue samples with In Stitu Cell Death Detection kit (Roche, Mannheim, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…After 4 weeks of treatment, mice were killed by cervical dislocation, and tumour tissues were harvested and fixed in 4% paraformaldehyde or frozen at −80°C. Histological, immunohistochemical and immunofluorescence analyses were performed as described . TdT‐mediated dUTP nick‐end labelling (TUNEL) analysis was used to detect the dead cells in the tissue samples with In Stitu Cell Death Detection kit (Roche, Mannheim, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The tumors were excised and were either formalin-fixed or flash-frozen at − 20°C. H&E, TUNEL, and immunohistochemical analyses were performed as previously described [30].…”
Section: Xenograft Assaymentioning
confidence: 99%
“…Many studies showed the multi-biological functions of ursolic acid, including anti-oxidant and anti-inflammatory activity 16. Also, ursolic acid has anti-cancer activity by inhibiting proliferation and stimulating apoptosis in prostate cancer 17, 18, colon cancer 19, 20, breast cancer 21, ovarian cancer 22, leukemia 23 and melanoma 24.…”
Section: Introductionmentioning
confidence: 99%